The influence of organizational characteristics, task division, job satisfaction and employee behavior on the work performance of employees of the regional revenue agency of muara enim district. - Nadia Purnama Sari; Sulbahri Madjir; Yusnawati Yusnawati (Penerbit Jurnal Indonesia, 2023)
The research method used in this research is a quantitative method using questionnaires distributed to respondents. Test data quality using validity tests, reliability tests, normality tests. The analysis used is descriptive analysis and inferential analysis using statistical calculations with multiple regression formulas, partial simultaneous tests and coefficient of determination. Organizational characteristics have a significant effect on the work performance of Muara Enim Regency Regional Revenue Agency employees. The division of tasks has a significant effect on the work performance of Muara Enim Regency Regional Revenue Agency employees. Job satisfaction has a significant effect on the work performance of Muara Enim Regency Regional Revenue Agency employees. Employee behavior has a significant effect on the work performance of Muara Enim Regency Regional Revenue Agency employees. Organizational Characteristics, Division of Tasks, Job Satisfaction and Employee Behavior together have a significant effect on the work performance of Muara Enim Regency Regional Revenue Agency employees.